RELIGIOUS MODERATION ON THE POLICE DISCRETION TO FACE THE STREET CRIMES (International Conference on Social and Islamic Studies, 2022)
This research aims to optimize the application of police discretion by internalizing the concept of religious moderation in dealing with street crimes by police officers. The emergence of street crimes with various criminal acts, such as theft and bribery have greatly disturbed the public so that a new formulation is needed to fix this condition. Furthermore, the internalization of the fair and balanced principle of religious moderation in the police discretion is able to optimize the performance of the police officers in carrying out their duties, including the application of discretion carefully and in accordance with legal regulations. This research is qualitative research which is described descriptively. The data collection technique used was interviewed. The results showed that the concept of religious moderation gave positive results in the application of police discretion. The positive results are: 1) Religious moderation has succeeded in being present as controllers and supervisors from within (internally) of the individual policeman in every discretionary action against the motorcycle gang members; 2) The concept of religious moderation helps police officers understand Islam and the importance of being moderate towards followers of other religions; 3) Increase community satisfaction with the performance of the police institution.